Environmental and maternal factors associated with gross placental morphology in dairy cattle. (7th December 2016) - Kamal, MM; Van Eetvelde, M; Vandaele, L; Opsomer, G
Contents: This article reports on a study of gross placental morphology of 282 expelled placentas from 89 primi‐ and 193 multiparous Holstein dams immediately after calving and examines associations with environmental factors such as typical herd features and season of calving, and maternal factors such as age at calving, level of milk yield at conception and cumulative amount of milk produced during gestation. The highest correlation between calf measurements and placental characteristics was found between the weight of the calf and the total cotyledonary surface ( r  = .643; p  < .001), confirming the high importance of the cotyledonary surface available for nutrient transfer to the developing foetus. Younger age in adolescent and smaller heart girth in multiparous dams were associated with a higher cotyledon number, suggesting placental compensation in dams with lower capacities in terms of dry matter intake. No significant association between milk yield during gestation in multiparous animals and gross placental morphometrics could be detected, indicating that factors such as the amount of milk produced during gestation affect placental development less than foetal weight close to term. Therefore, placental growth may be sustained at the expense of other tissues in an attempt to maintain pregnancy and minimize the adverse consequences for the foetus. This study offers evidence concerning factors affecting the placental surface size for nutrient transfer from dam to calf in dairy cattle based on gross morphometrics, but needs confirmation from studies in which this surface size is more profoundly assessed by measuring the branches present in the cotyledonary villi.